A bibliometric analysis of autophagy in atherosclerosis from 2012 to 2021 - Fengwei Zhang; Ruirui Wang; Baocheng Liu; Lei Zhang (Frontiers Media S.A., 2022)
Background: Regulation of autophagy affects the progression of atherosclerosis. In recent years, research on autophagy in atherosclerosis has been widely concerned. However, there is no bibliometric analysis in this field.Objective: The purpose of this study was to explore the general situation, hot spots, and trends of the research in this field through bibliometric analysis.Methods: Articles related to autophagy in atherosclerosis from 2012 to 2021 were retrieved from the Web of Science Core Collection. VOSviewer and CiteSpace were used for data analysis and visualization of countries, institutions, authors, keywords, journals, and citations.Results: A total of 988 articles were obtained in the last 10 years. The number of publications and citations increased rapidly from 2012 to 2021, especially after 2019. The most productive countries, institutions, journals, and authors were the People's Republic of China, Shandong University, Arteriosclerosis Thrombosis and Vascular Biology, and Wim Martinet, respectively. The primary keywords were "oxidative stress," "apoptosis," "activated protein kinase," and "inflammation." The burst detection analysis of keywords found that "SIRT1" and "long non-coding RNA" might be regarded as the focus of future research.Conclusion: This is the first bibliometric analysis of autophagy in atherosclerosis, which reports the hot spots and emerging trends. The interaction between oxidative stress and autophagy, programmed cell death, and activated protein kinases are considered to be the current research priorities. Molecular mechanisms and therapeutic target for the intervention of atherosclerosis by regulating autophagy will become an emerging research direction.